STATUS HUKUM KEPEMILIKAN RUMAH SUSUN DI ATAS HAK GUNA BANGUNAN OLEH WNA DALAM HUKUM POSITIF (LEGAL STATUS OF FLOWER OWNERSHIP ABOVE BUILDING USE RIGHTS BY FOREIGNERS IN POSITIVE LAW) - Febrinaty, Yenny; ,, Ariyanto; Sari, Mayzara (PALAR (Pakuan Law review), 2024)
Abstract Following the implementation of the Job Creation Law, there has been an increase in the demand for housing from foreigners. Nonetheless, this situation raises issues, particularly concerning the control of ownership rights to condominiums or apartments by foreign nationals. This research examines the legal status of apartment ownership above Building Use Rights held by foreigners and comprehends the ownership of apartments by foreigners, considering the principle of nationalism in positive law. The research method employed is normative legal research with a qualitative approach. The primary sources of data consist of various literature and legislation relevant to this study. The research findings indicate that the Job Creation Law has acknowledged the status of ownership rights to apartment units for foreign nationals. However, in practice, it appears to neglect the principle of Nationality Principle as stipulated in the Basic Agrarian Law. Therefore, the Government must reassess this policy, as state land should be utilized and prioritized in the best possible manner for the welfare of all Indonesian citizens. Keywords: foreigners, flats, legal status. Abstrak Setelah diberlakukannya UU Cipta Kerja, permintaan akan hunian oleh orang asing semakin meningkat. Namun, situasi ini menimbulkan masalah terutama dalam penguasaan hak milik atas unit rumah susun atau apartemen oleh Warga Negara Asing. Studi ini tujuannya guna analisis status hukum kepemilikan rumah susun di atas Hak Guna Bangunan oleh WNA serta untuk memahami kepemilikan rumah susun oleh WNA dengan mempertimbangkan asas nasionalisme dalam hukum positif. Metode penelitian disini ialah penelitian hukum normatif dengan pendekatan kualitatif. Sumber data utama adalah berbagai literatur dan perUUan terkait studi ini. Hasil studi memperlihatkan UU Cipta Kerja telah mengakui status hak kepemilikan unit rumah susun oleh Warga Negara Asing. Namun, dalam praktiknya, hal ini terlihat mengabaikan prinsip Asas Nasionalitas yang tercantum pada UU Pokok Agraria. Oleh karena itu, Pemerintah perlu melakukan kajian ulang pada kebijakan ini, karena tanah negara seharusnya dimanfaatkan dan diutamakan sebaik mungkin bagi kepentingan seluruh warga Negara Indonesia. Kata kunci: orang asing, rumah susun, status hukum.